If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+5)=2(3x+3)
We move all terms to the left:
3(x+5)-(2(3x+3))=0
We multiply parentheses
3x-(2(3x+3))+15=0
We calculate terms in parentheses: -(2(3x+3)), so:We get rid of parentheses
2(3x+3)
We multiply parentheses
6x+6
Back to the equation:
-(6x+6)
3x-6x-6+15=0
We add all the numbers together, and all the variables
-3x+9=0
We move all terms containing x to the left, all other terms to the right
-3x=-9
x=-9/-3
x=+3
| 40/2x=6 | | 75=15(2y+1 | | 50=8x/120 | | 20=h3+ 17 | | 2534+25.5x=70.75x | | 11x-17=5x+13 | | 16t+4(5–t)=8 | | -7/x+x+7/3=1 | | -2=x/3+5 | | 4x-34=x+86 | | u-4/5=72/3 | | x+0.99=42.72 | | 3x+22+90+2x+38=180 | | 1=5(x+3)+2x | | z4+ 3=6 | | 8x-10=8x/30 | | 6(3–x)=54 | | •10+3x=35 | | j/40=5/4 | | 2*(x+12)=20 | | .4x-6=38 | | 1/7x-5/2=-5/3 | | -14m-(-18)=4 | | |2z+1|-6=8 | | 8*(x+10)=24 | | 2x-58+2x+6=180 | | 3x+5=7x−27 | | 17-x=-3+7 | | x/10+17=19 | | 2.3(x–1)+10=7x–5 | | 3x²-5x=-4 | | z−162=−2 |